Smiling in the face of precarity: housing and eviction in Hangberg, South Africa - Buhler, Andreas Joachim (Social Anthropology, 2014)
Much has been written about housing and eviction in South Africa, and they are issues present throughout most of South Africa's recent history. The demolition of places such as Sophiatown or District Six has become some of the most common imagery reflecting the brutality of apartheid South Africa. Yet, evictions and a lack of affordable housing, has been a common feature of the post-apartheid South African city as well. In Hangberg evictions and housing where part of the struggle of ordinary life. With a lack of affordable housing the people living in Hangberg had started to build houses of their own, which in turn made them targets for evictions. To build a house for yourself meant that you might risk violent reprisals from the state. Thus suffering was part of ordinary for the people I worked with. In the midst of suffering, however, they still aspired towards bettering their lives. I follow Chabal's (2009) argument that it is necessary to both recognise the ways in which people smile and suffer. This is to recognise and honour the ways in which people cope with their suffering. I argue that their smiling can be framed through the notion of agency and aspirations, and their suffering can be framed with the concept of precarity. Focusing on smiling and aspiring allows for an understanding of the capacity which people have to improve their own lives. It is in my opinion a tool for empowering people's voices and agency. Precarity allows us, on the other hand, to understand the multiplicity of constriction and oppression. Through an ethnographic study of housing and eviction in Hangberg, both precarity and aspirations are brought forward as processes shaping human existence. Through their aspirations the people I worked with smiled at the precarity they faced in their ordinary lives. They built houses they were proud of;; houses that they imagined would protect them from the sickness and suffering they experienced. Their houses were both a way of improving their lives, but also an attempt at creating a home in Hangberg and a sense of stability. I also reflect on the affect the distribution of precarity had on the people of Hangeberg as subjects of the state.